2007
DOI: 10.2310/6650.2007.06029
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Concentrations in Bone Marrow of Stable Sickle Cell Anemia Patients

Abstract: Inflammation plays a significant role in the clinical manifestations of sickle cell anemia. In studies of anemic patients with other clinical syndromes, measurement of the concentrations of cytokine mediators of inflammation in bone marrow aspirates has provided unique correlations with clinical and laboratory parameters. We determined concentrations of interleukin (IL)-1, IL-6, tumor necrosis factor (TNF), and placental growth factor (PlGF) in bone marrow aspirates from six homozygous sickle cell (SS) patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…SCD has been described as a chronic inflammatory state, with elevated leukocyte counts, increased serum levels of C-reactive protein and cytokines [8, 9], and a propensity for erythrocyte and platelet activation [10], all processes that might be exacerbated by G-CSF usage. A number of prospective clinical trials have demonstrated a correlation between leukocytosis and sickle-related complications including increased mortality [1113].…”
Section: Plausible Determinants Of Scd-related G-csf Complicationsmentioning
confidence: 99%
“…SCD has been described as a chronic inflammatory state, with elevated leukocyte counts, increased serum levels of C-reactive protein and cytokines [8, 9], and a propensity for erythrocyte and platelet activation [10], all processes that might be exacerbated by G-CSF usage. A number of prospective clinical trials have demonstrated a correlation between leukocytosis and sickle-related complications including increased mortality [1113].…”
Section: Plausible Determinants Of Scd-related G-csf Complicationsmentioning
confidence: 99%
“…It is a cytokine that appears to distinguish SS patients from healthy controls(9); it is produced by erythroid cells(9); and it is measurable in marrow aspirate plasma at higher concentrations than are seen in concurrent serum or plasma samples(11). The experiments in this report demonstrate that CFU-E colony formation from SS patients is relatively resistant to inhibition by rhγIFN, and that the addition of rhPlGF to cell cultures can confer this resistance phenotype on CFU-E from the marrow of healthy control subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Other investigators found similar results, but only during acute painful crises(10). In studies of the contribution of inflammatory cytokines to the regulation of erythropoiesis in homozygous sickle cell (SS) patients, we measured concentrations of PlGF, interleukin (IL)-1, IL-6, tumor necrosis factor (TNF) and γ interferon (IFN) in marrow aspirates from steady-state, low severity SS patients and healthy volunteer control subjects(11). Marrow aspirate PlGF concentrations were significantly higher in SS patients than in controls; there were no differences in the other cytokines measured.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation